An Integrated Communication Message Framework of Inter-Vehicles for Connected Vehicles using Mobile Virtual Fence(MVF) - Kim, Inhwan; Yoo, Hyunmi; Young-Hyun, Eom; Cho, Sungguk; Jeon, Byungkook (International Journal of Engineering & Technology, 2018)
In this paper, we present an integrated message framework of BSM and CAM/DENM as safety messages for V2X communications of connected vehicles in VANETs, and apply it to the mobile virtual fence(MVF), which has been preliminarily researched and developed. To do this, the proposed message framework become united an integrated framework adding up context-aware information of the MVF after comparing and analyzing whether or not the common fields between are. And then, the integrated messages are parsed according to the type of original messages at the destination such as vehicles, ITS(Intelligent Transportation Systems), pedestrians that it received.Â